2020
DOI: 10.1073/pnas.2017094117
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transfer of DNA methylation marks in the honey bee

Abstract: The evolutionary significance of epigenetic inheritance is controversial. While epigenetic marks such as DNA methylation can affect gene function and change in response to environmental conditions, their role as carriers of heritable information is often considered anecdotal. Indeed, near-complete DNA methylation reprogramming, as occurs during mammalian embryogenesis, is a major hindrance for the transmission of nongenetic information between generations. Yet it remains unclear how general DNA methylation rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 71 publications
(108 reference statements)
4
76
0
Order By: Relevance
“…This may reflect the small number of maternal and paternal epialleles predicted for polyandrous insects (59). Interestingly, the colony-specific methylation patterns are inherited from drones to their worker daughters (40), suggesting a role for the paternally inherited epialleles to the composition of colony-specific worker methylomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may reflect the small number of maternal and paternal epialleles predicted for polyandrous insects (59). Interestingly, the colony-specific methylation patterns are inherited from drones to their worker daughters (40), suggesting a role for the paternally inherited epialleles to the composition of colony-specific worker methylomes.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the knockdown of the Dnmt3 gene function, a key orchestrator of honey bee development, is lethal at early development (16) suggests that DNA methylation is essential to honey bee viability. Furthermore, the colony-specific methylation patterns are, at least in part, sequence-specific (32,39,40). Ultra-deep amplicon sequencing analyses identified that a honey bee brain displays only a small repertoire of methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation is that population differences in DNA methylation could have arisen randomly ( i.e ., epimutations) and then been selected by the environment. This could be made more possible in insects by the reported high heritability of arthropod gene body methylation (Liew et al, 2020; Yagound et al, 2020). Indeed, theoretical models have shown that stochastic but heritable epigenetic variation can be adaptive under changing environments (Feinberg & Irizarry, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation and histone post-translational modifications are the most wellstudied among these mechanisms (Smallwood and Kelsey, 2012;Paredes et al, 2016). Not all insects possess appreciable levels of DNA methylation (Deobagkar, 2018;Deshmukh et al, 2018), but some, including many social insects, do (Li-Byarlay, 2016;Yagound et al, 2020). Some studies show that developmental experience-induced changes in DNA methylation impact adult behavioral phenotypes (Linksvayer et al, 2012;Patalano et al, 2012;Weiner and Toth, 2012;Yan et al, 2014;Alvarado et al, 2015).…”
Section: Homology Of Function In Neural Mechanisms That Encode Develomentioning
confidence: 99%